Intraoperative Magnetic Resonance Imaging Assisted Endoscopic Endonasal Resection of Clival Chordomas - Gulsuna, Beste; Karaaslan, Burak; Kaymaz, Memduh; Emmez, Hakan; Cindil, Emetullah; Sahin, Muammer Melih; Celtikci, Emrah (Frontiers in Oncology, 2022)
Background: Cranial base chordomas are typically indolent and usually appear as encapsulated tumors. They slowly grow by infiltrating the bone, along with the lines of least resistance. Due to its relationship with important neurovascular structures, skull base chordoma surgery is challenging. Objective: The usefulness of intraoperative magnetic resonance imaging (IO-MRI) in achieving the goal of surgery, is evaluated in this study. Methods: Between March 2018 and March 2020, 42 patients were operated on for resection of skull base chordomas in our institution. All of them were operated on under IO-MRI. Patients were analyzed retrospectively for identifying common residue locations, complications and early post-operative outcomes. Results: In 22 patients (52%) gross total resection was achieved according to the final IO-MRI. In 20 patients (47%) complete tumor removal was not possible because of extension to the petrous bone (8 patients), pontocerebellar angle (6 patients), prepontin intradural (4 patients), temporobasal (1 patient), cervical axis (1 patient). In 13 patients, the surgery was continued after the first IO-MRI control was performed, which showed a resectable residual tumor. 7 of these patients achieved total resection according to the second IO-MRI, in the other 6 patients all efforts were made to ensure maximal resection of the tumor as much as possible without morbidity. Repeated IO-MRI helped achieve gross total resection in 7 patients (53.8%). Conclusions: Our study proves that the use of IO-MRI is a safe method that provides the opportunity to show the degree of resection in skull base chordomas and to evaluate the volume and location of the residual tumor intraoperatively. Hence IO-MRI can improve the life expectancy of patients because it provides an opportunity for both gross total resection and maximal resection in cases where total resection is not possible.